High transparency Pr:Y₂O₃ ceramics: a promising gain medium for red emission solid-state lasers - Li, Qing (2023)
Highly transparent 0.5 and 1.0 at% Pr-doped Y2O3 ceramics were fabricated by vacuum sintering plus hot isostatic pressing (HIP) treatment. The selection of suitable pre-sintering temperatures and right microstructures before HIP was critical to obtain high density of the final sintered bodies. The well-densified ceramics had pore-free microstructures with an average grain size of about 1 µm. It was also found that the charge states of the Pr ions could be changed through regulating the annealing atmospheres, resulting in different absorption and emission characteristics in the visible wavelength region. Annealing in reducing atmosphere (5% H2/95% Ar) favored the formation of Pr3+, resulting in stronger red emissions, while annealing in oxygen atmosphere led to the rise of lattice constant due to the concentration increase of oxygen interstitials. The H2/Ar-annealed 0.5 at% Pr:Y2O3 ceramics exhibited strong red emission at 600–675 nm, which may be a promising gain material for red solid-state lasers.